Hubungan Inovasi Posyandu dengan Keaktifan Kader dan Kunjungan Balita di Posyandu Cempaka Desa Nganguk Kudus - Zulaekah, Niar; Astuti, Dwi; Tristanti, Ika (Midwifery Care Journal, 2025)
Â Posyandu (Integrated Health Service Post) is a form of community-based health service aimed at improving health status, particularly for toddlers, pregnant women, and breastfeeding mothers. One of the challenges in managing Posyandu is increasing the number of toddler visits and the activity level of cadres in delivering services. Low toddler visit rates and inactive cadres are common issues faced by Posyandu. The success of Posyandu often depends on the active role of cadres, who are the main drivers of Posyandu activities. The success of Posyandu is significantly influenced by the participation of active and competent cadres.In response to this challenge, Nganguk Village created the "KITA OKE" Posyandu innovation. The objective of this study is to analyze the relationship between Posyandu innovation, cadre activity, and toddler visits. This research uses a quantitative method with a correlational approach and a saturated sampling technique, meaning that all members of the population are included as the research sample. As a result, all 40 cadres were selected as respondents. Data collection was conducted using questionnaires and observations during Posyandu sessions. Statistical data analysis in this study employed the chi-square test. The results of this study indicate that the implementation of innovation at Posyandu positively correlates with cadre activity but does not directly affect toddler visit rates. It can be concluded that there is a relationship between innovation and cadre activity, but there is no relationship between Posyandu innovation and toddler visits.